2014
DOI: 10.1002/chem.201303729
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Luminous Tetranuclear Gold(I) Complexes Supported by Tetraphosphine Ligands, meso‐ or rac‐Bis[(diphenylphosphinomethyl)phenylphosphino]methane

Abstract: A series of tetragold(I) complexes supported by tetraphosphine ligands, meso- and rac-bis[(diphenylphosphinomethyl)phenylphosphino]methane (meso- and rac-dpmppm) were synthesized and characterized to show that the tetranuclear Au(I) alignment varies depending on syn- and anti-arrangements of the two dpmppm ligands with respect to the metal chain. The structures of syn-[Au4 (meso-dpmppm)2X]X'3 (X = Cl; X' = Cl (4 a), PF6 (4 b), BF4 (4 c)) and syn-[Au4 (meso-dpmppm)2]X4 (X = PF6 (4 d), BF4 (4 e), TfO (4 f); TfO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 161 publications
(81 reference statements)
2
59
0
Order By: Relevance
“…[33] Furthermore, both gold atoms feature an approximately linear coordination mode (C1-Au1-Cl1 177.4(3) and P1-Au2-Cl2 174.33 (8)), which is commonly ob- 10 dispersion interaction is not present based on their large distance (d(Au1ÀAu2) = 6.8181(2) ). A closer look at the extended solid-state structure reveals a weak goldgold interaction, which is commonly termed as unsupported aurophilicity (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…[33] Furthermore, both gold atoms feature an approximately linear coordination mode (C1-Au1-Cl1 177.4(3) and P1-Au2-Cl2 174.33 (8)), which is commonly ob- 10 dispersion interaction is not present based on their large distance (d(Au1ÀAu2) = 6.8181(2) ). A closer look at the extended solid-state structure reveals a weak goldgold interaction, which is commonly termed as unsupported aurophilicity (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…To increase the number of metal atoms, we have developed a linear tetraphosphine, meso ‐bis[(diphenylphosphino‐methyl)phenylphosphino]methane ( meso ‐dpmppm; Scheme a, left), and it was recently disclosed that tetrapalladium units supported by two meso ‐dpmppm ligands, {Pd 4 (μ‐ meso ‐dpmppm) 2 } 2+ , are thermodynamically self‐aligned into a linear octapalladium array of {Pd 8 (μ‐ meso ‐dpmppm) 4 } 4+ in the solution state, which was isolated as discrete molecules of [Pd 8 (μ‐ meso ‐dpmppm) 4 ](BF 4 ) 4 ( 1 ) and [Pd 8 (μ‐ meso ‐dpmppm) 4 L 2 ](BF 4 ) 4 (L=XylNC ( 2 ), CH 3 CN ( 3 ), dmf ( 4 ); Scheme b) . In the present study, we have utilized rac ‐dpmppm (Scheme a, right), which is a stereoisomer of meso ‐dpmppm ( RS ) and consists of an equimolar mixture of ( RR ) and ( SS ) enantiomers with respect to the chiral centers at the inner two phosphine units, and synthesized linear octapalladium chains supported by homochiral tetraphosphines, [Pd 8 (μ‐ rac ‐dpmppm) 4 L 2 ](BF 4 ) 4 (L=CH 3 CN ( 6 ), dmf ( 7 ), XylNC ( 8 )), [Pd 8 (μ‐ rac ‐dpmppm) 4 ](BF 4 ) 4 ( 9 ), and [Pd 8 (μ‐ rac ‐dpmppm) 4 (Cl) 2 ](BF 4 ) 2 ( 10 ). Furthermore, variable‐temperature NMR studies for a 1:1 mixture of 7 (with rac ‐dpmppm) and 4 (with meso ‐dpmppm) revealed unprecedented chiral self‐recognition between the Pd 4 units of {Pd 4 (μ‐ rac ‐dpmppm) 2 } 2+ and {Pd 4 (μ‐ meso ‐dpmppm) 2 } 2+ to restore the Pd 8 chains with homochiral ligands at lower temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The structure shows that both benzene rings of the paracyclophane backbone are in nearly coplanar arrangement. The Au1−Cl1 and Au1−P1 bond lengths (2.313(3) Å and 2.232(3) Å) are in the expected region . The gold atom shows a linear coordination sphere with a P1‐Au1‐Cl1 bonding angle of 173.7° that only slightly differs from the ideal 180° typically observed for gold(I) compounds.…”
Section: Resultsmentioning
confidence: 76%